Difficulties and Solutions in Learning Qowaid Nahwu for Beginners: A Case Study - Oktafian Holilullah; Yayah Robiatul Adawiyah (Universitas Pahlawan Tuanku Tambusai, 2026)
Learning qowaid nahwu (Arabic grammar) at the beginner level is often challenging because students must understand abstract grammatical concepts and apply complex linguistic rules in authentic language use. This study aims to identify the learning difficulties experienced by beginner students at LPBA Nurul Jadid, examine the factors contributing to these difficulties, and explore the pedagogical strategies employed to address them. The study adopted a post-positivist paradigm using a qualitative case study approach. Data were collected through classroom observations, semi-structured interviews, diagnostic tests, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that students experienced difficulties in understanding i‘rab rules, distinguishing between jumlah ismiyyah and jumlah fi‘liyyah, applying grammatical rules in context, and determining correct word-final inflections. These challenges were attributed to memorization-oriented instruction, limited visual learning resources, and insufficient scaffolded practice. To overcome these problems, instructors implemented i‘rab charts, structured drills, gradual scaffolding, and contextualized communicative activities. These pedagogical strategies improved students’ grammatical understanding and facilitated more effective application of nahwu rules in practical Arabic communication.